PEMBERIAN SANKSI REHABILITASI BAGI PENYALAHGUNA NARKOTIKA BERDASARKAN PASAL 127 DIKAITKAN DENGAN PASAL 103 UNDANG-UNDANG NOMOR 35 TAHUN2009 TENTANG NARKOTIKA - Thika Shalsabillah; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In decision No. 1243/Pid.Sus/2022/PN.Sby the defendant was declared legallyand convincingly guilty of committing the crime of class I Narcotics abuse for himself.The Defendant was given a criminal sanction in the form of imprisonment for 2 (two)years but the Judge did not order or implement rehabilitation for the Defendant.Whereas in Article 127 paragraph (3) of Law No. 35 of 2009 clearly states that: "In theevent that the abuser as referred to in paragraph (1) can be proven or proven to be avictim of narcotics abuse, the abuser is required to undergo medical rehabilitation andsocial rehabilitation." Thus the judge's decision does not reflect legal certainty.The type of legal research is normative legal research. The data used issecondary data. Meanwhile, if seen from the nature of this research is descriptive.The results of this study are that the provision of rehabilitation sanctions fornarcotics abusers based on Article 127 is linked to Article 103 of Law Number 35 of2009 concerning Narcotics, namely judges often do not give rights to narcotics users tocarry out rehabilitation, even though in Law Number 35 of 2009 concerning Narcoticsthere is a guarantee rehabilitation for drug abusers. This article should be used as abasis for judges deciding cases of narcotics abuse for users and addicts to undergomedical rehabilitation and social rehabilitation aimed at recovering perpetrators fromnarcotics addiction. Legal certainty regarding the imposition of rehabilitation sanctionsbased on Article 127 is linked to Article 103 of Law Number 35 of 2009 concerningNarcotics against abusers and perpetrators of criminal acts, namely Law Number 35 of2009 concerning Narcotics has provided legal certainty for the sanctions given, namelyin the form of imprisonment (prison) and rehabilitation sanctions (medical and social)for each perpetrator. Law Number 35 of 2009 concerning Narcotics has 2 sides, namelya humanist side for narcotics addicts and abusers, and a tough and firm side fordealers, syndicates and narcotics dealers. However, what needs attention in itsimplementation is that imprisonment given to narcotics abusers is not an effective wayto repair damage.Keywords: Sanctions, Rehabilitation, Narcotics Abuse